The Influence of Leadership on Employee Performance In Class IIA Central Institution, Karawang - Bambang Nurakhim; Harries Madiistriyatno; Aji Wijayanto (Return : Study of Management, Economic and Bussines, 2023)
In this study, there are two variables, namely Variable X (Leadership) and Variable Y (Performance). This research was conducted to determine the Leadership at the Class IIA Karawang Penitentiary, Employee Performance at the Class IIA Penitentiary Karawang. The method used in this research is descriptive analysis method to discuss the problem formulation of how Leadership in Correctional Class IIA Karawang and employee performance at Correctional Class IIA Karawang, and verification analysis to discuss the formulation of the problem of how much influence Leadership has on Employee Performance in Class Penitentiary. IIA Karawang. The data used are primary and secondary data collected through observation, interviews, questionnaires (questionnaires), and literature. The hypothesis of this research is that there is an influence of leadership on employee performance in Correctional Institution class IIA Karawang. To measure the magnitude of the effect of these variables, Simple Linear Regression and Correlation Coefficients and Coefficients of Determination were used with the help of the IBM SPSS application program. Based on the results of data analysis using statistical methods, namely Simple Linear Regression, the Coefficient of Determination (KD) value is 0.45. Based on these results, it can be concluded that Leadership has an effect on Employee Performance at the Class IIA Karawang Penitentiary.